Earlier and more specific detection of persistent neck disease with diffusion‐weighted MRI versus subsequent PET/CT after definitive chemoradiation for oropharyngeal squamous cell carcinoma. Issue 3 (11th October 2016) - Yu, Yao; Mabray, Marc; Silveira, William; Shen, Peter Y.; Ryan, William R.; Uzelac, Alina; Yom, Sue S.
Abstract: Background: The purpose of this study was to test if diffusion‐weighted imaging (DWI) identified persistent neck disease after chemoradiotherapy (CRT) for oropharyngeal cancer earlier and as accurately as subsequent positron emission tomography (PET)/CT. Methods: We performed a review of patients with oropharyngeal cancer treated with definitive CRT who underwent DWI and PET/CT at a median of 8 and 14 weeks posttreatment. Imaging characteristics were correlated with pathologically proven neck failure. Results: Forty‐one patients and 58 hemi‐necks were analyzed. With a median follow‐up of 120 weeks, 4 neck failures were identified. The apparent diffusion coefficient (ADC) of lymph node failures was lower (1220 vs 1910 μm 2 /s; p = .003) than non‐failures. Using an ADC threshold of 1500 μm 2 /s, the sensitivity, specificity, and positive and negative predictive values (PPV; NPV) were 100% (4/4), 92% (46/50), 50% (4/8), and 100% (46/46) for DWI, respectively, and 100% (3/3), 71% (22/31), 25% (3/12), and 100% (22/22) for PET/CT, respectively. Conclusion: Earlier DWI produced similar sensitivity and better specificity in identifying persistent neck disease as 3‐month PET/CT. © 2016 Wiley Periodicals, Inc. Head Neck 39: 432–438, 2017